Sources and rates of organic substrates in the production of pear Cascatense on quince ‘CP’ - Verlindo, Andricia; Biasi, Luiz Antonio; Botelho, Renato Vasconcelos; Müller, Marcelo Marques Lopes (Comunicata Scientiae, 2022)
The nutritional state of cultivated plants can be influenced, due to the poultry litter doses and basalt powder, thus affecting its proper growth. This work aimed to evaluate the nutritional efficiency of pear, cultivated in different poultry litter doses and basalt powder. The experiment was conducted in the orchard of the fruit growing sector of the Department of Agronomy at the Universidade Estadual do Centro-Oeste, Guarapuava- PR, in 2010, spaced 2.5 x 0.5 m, with the following treatments in the planting hole and reapplied in August of 2012: T1) without fertilization; T2) 2 kg of poultry litter; T3) 2 kg of poultry litter + 2 kg of basalt powder; T4) 4 kg of poultry litter; T5) 4 kg of poultry litter + 2 kg of basalt powder. Samples of the root system, and the shoot segmented in side branches and trunk were collected in January / 2014 (1,190 days) for chemical analysis of nutrient content and dry matter. With these results were calculated the indexes: absorption efficiency; transport efficiency and nutrient utilization efficiency. The treatment 4 kg of poultry litter, result in a higher absorption efficiency ratio for N, and higher utilization efficiency index for S. The transport efficiency suffered a little variation due to the used doses.